2017
DOI: 10.1002/cncr.30792
|View full text |Cite|
|
Sign up to set email alerts
|

Multisite external validation of a risk prediction model for the diagnosis of blood stream infections in febrile pediatric oncology patients without severe neutropenia

Abstract: Background Pediatric oncology patients are at increased risk for invasive bacterial infection due to immunosuppression. The risk of such infection in the absence of severe neutropenia (absolute neutrophil count (ANC) ≥500/μl) is not well established and a validated prediction model for blood stream infection (BSI) risk offers clinical utility. Methods A six-site retrospective external validation was conducted using a previously published risk prediction model for BSI in febrile pediatric oncology patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 21 publications
5
52
0
Order By: Relevance
“…The majority of patients discharged home after initial evaluation without antibiotics with no adverse consequences. The overall incidence of positive blood culture was 3.4%, comparable to other similar‐sized cohorts of 3.1% to 3.6% . Other studies have found higher incidence ranging 6.1% to 10.9%, although these studies only included patients with CVCs.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The majority of patients discharged home after initial evaluation without antibiotics with no adverse consequences. The overall incidence of positive blood culture was 3.4%, comparable to other similar‐sized cohorts of 3.1% to 3.6% . Other studies have found higher incidence ranging 6.1% to 10.9%, although these studies only included patients with CVCs.…”
Section: Discussionsupporting
confidence: 66%
“…If accounting for patients with CVCs alone, the incidence of positive blood culture in our study was 3.0% (6/203). Previous studies have proposed that characteristics such as height of fever, externalized CVCs, and absence of viral respiratory symptoms are associated with bacteremia. Our study demonstrated no significant differences in clinical variables between patients with and without positive blood cultures aside from rate of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 646 titles and abstracts were reviewed, of which 83 full‐text articles were retrieved. From this, 16 relevant articles, describing 15 studies, were identified for inclusion in this review (Figure ) . No dedicated NNF treatment guidelines were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria across the studies included in this review varied. Notably, nine (60%) studies only included patients with a central venous catheter (CVC) in situ . The type of CVC also varied across the studies with implanted ports more common in six, whereas tunneled external CVC were more common in two, albeit older, studies (type not reported in 7).…”
Section: Resultsmentioning
confidence: 99%